Analisis Kemampuan Membaca Al-Qur’an Siswa Kelas IV pada Mata Pelajaran Al-Qur’an Hadis di Mi Nurul Mujahidin Selong Belanak Tahun Pelajaran 2025/2026 - Hauli Kamariah; Ridwan; Lalu Asriadi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to analyze the Qur’an reading ability of fourth-grade students in the Al-Qur’an Hadith subject at MI Nurul Mujahidin Selong Belanak in the 2025/2026 academic year. This research employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The research subjects consisted of the principal, the Al-Qur’an Hadith teacher, and fourth-grade students. The findings revealed that the students’ Qur’an reading ability was categorized as adequate. Some students were able to read the Qur’an fluently and apply basic tajwid rules correctly; however, several students still experienced difficulties in recognizing hijaiyah letters, pronouncing makharijul huruf accurately, and applying tajwid rules properly. The factors influencing students’ Qur’an reading ability included the lack of habituation in reading the Qur’an at home, low learning motivation, and limited parental support. Teachers’ efforts to improve students’ Qur’an reading ability were carried out through habituation activities before learning, special guidance for students with difficulties, the use of talaqqi and demonstration methods, and providing motivation to students. These efforts gradually improved the students’ Qur’an reading ability.